Antibody avidity to pertussis toxin after acellular pertussis vaccination and infection - Knuutila Aapo; Dalby Tine; Ahvenainen Niina; Barkoff Alex-Mikael; Jørgensen Charlotte Sværke; Fuursted Kurt; Mertsola Jussi; He Qiushui (United Kingdom, 2025)
Pertussis toxin (PT) is a unique virulence factor of Bordetella pertussis, and therefore a key component of acellular pertussis vaccines. Although immunity after infection seems to persist longer than after vaccination, the exact mechanisms are not fully known. In this study the overall binding strength (avidity) of anti-PT IgG antibodies was compared after acellular booster vaccination and infection, as a parameter to evaluate long-lasting protection.
Danish and Finnish serum samples from a total of 134 serologically confirmed patients and 112 children who received acellular booster vaccines were included in this study. The concentration of anti-PT IgG was first determined by ELISA, followed by two separate ELISAs to evaluate antibody avidity: either with a dilution series of urea as a bond-breaking agent of antibody and antigen binding and a constant anti-PT IgG concentration between the samples or with a constant dilution ratio of sera and detergent. In addition to urea, the use of diethylamine and ammonium thiocyanate as disruptive agents were first compared between each other.
A strong Spearman correlation (R > 0.801) was noted between avidity and concentration of anti-PT IgG antibodies if a constant serum dilution method was used, and avidity was noted to be higher in patients in comparison to vaccinees in Denmark, but not in Finland. However, no correlation between antibody concentration and avidity was found if a constant anti-PT IgG concentration was used (R = -0.157). With this method, avidity after vaccination was significantly higher in comparison to that after infection in both Danish and Finnish subjects (p < 0.01). A shorter time since the latest booster vaccination was found to affect avidity positively on the next PT-antigen exposure with either vaccination or infection.